RETRACTED: “Atypical child” in an educational environment in the Murmansk region - Zhigunova Galina; Afonkina Yulia (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 84, 00001 (2024), https://doi.org/10.1051/bioconf/20248400001